Unexplained mortality during the US COVID-19 pandemic: retrospective analysis of death certificate data and critical assessment of excess death calculations - Kathleen A Fairman; Kellie J Goodlet; James D Rucker; Roy S Zawadzki (BMJ Open, 2021)
Objectives Cause-of-death discrepancies are common in respiratory illness-related mortality. A standard epidemiological metric, excess all-cause death, is unaffected by these discrepancies but provides no actionable policy information when increased all-cause mortality is unexplained by reported specific causes. To assess the contribution of unexplained mortality to the excess death metric, we parsed excess deaths in the COVID-19 pandemic into changes in explained versus unexplained (unreported or unspecified) causes.Design Retrospective repeated cross-sectional analysis, US death certificate data for six influenza seasons beginning October 2014, comparing population-adjusted historical benchmarks from the previous two, three and five seasons with 2019–2020.Setting 48 of 50 states with complete data.Participants 16.3 million deaths in 312 weeks, reported in categories—all causes, top eight natural causes and respiratory causes including COVID-19.Outcome measures Change in population-adjusted counts of deaths from seasonal benchmarks to 2019–2020, from all causes (ie, total excess deaths) and from explained versus unexplained causes, reported for the season overall and for time periods defined a priori: pandemic awareness (19 January through 28 March); initial pandemic peak (29 March through 30 May) and pandemic post-peak (31 May through 26 September).Results Depending on seasonal benchmark, 287 957–306 267 excess deaths occurred through September 2020: 179 903 (58.7%–62.5%) attributed to COVID-19; 44 022–49 311 (15.2%–16.1%) to other reported causes; 64 032–77 054 (22.2%–25.2%) unexplained (unspecified or unreported cause). Unexplained deaths constituted 65.2%–72.5% of excess deaths from 19 January to 28 March and 14.1%–16.1% from 29 March through 30 May.Conclusions Unexplained mortality contributed substantially to US pandemic period excess deaths. Onset of unexplained mortality in February 2020 coincided with previously reported increases in psychotropic use, suggesting possible psychiatric or injurious causes. Because underlying causes of unexplained deaths may vary by group or region, results suggest excess death calculations provide limited actionable information, supporting previous calls for improved cause-of-death data to support evidence-based policy.